Environmental Disclosure and Tax Aggressiveness of Property and Real Estate Sector Companies: Evidence from Indonesia - Saraswatie, Nurina Oktaviani; San, Isnalita; Rahmiati, Alfa (International Journal of Psychosocial Rehabilitation, 2020)
There have been a lot of researches concerning the corporate social responsibility and tax aggressiveness in Indonesia. However, this study provides particular attention into the effects of environmental disclosure (corporate social responsibility) on tax aggressiveness on property and real estate sector companies. This study also provides a test using some control variables, such as company size (SIZE), and leverage (LEV) to robust the analysis. Based on 103 samples of Indonesian publicly listed property and real estate sector companies, the results indicate that corporate social responsibility firm significantly negative related to tax aggressiveness, while firm size and leverage surprisingly are not significantly related to tax aggressiveness.